-3x^2-24x-47

Thank you for the opportunity to help you with your question!

Vertex form is a form y=a(x-h)^2+k

Now

y=-3x^2-24x-47

y+47=-3x^2-24x

y+47=-3(x^2+8)

y+47-3[ ] = -3 (x^2+8x+1[ ])

y +47 -3[1]=--3 (x^2-2x+1[1 ])

y+47-3=-3(x^2-2x+1)

y=-3(x^2-2x+1)-44

y=-3(x-1)^2-44

Correction:I made a mistake in my previous answer. Here is corrected one.

y +47 -3[16]=--3 (x^2-8x+1[16 ])

y+47-48=-3(x^2-8x+16)

y-1=-3(x-4)^2

Comparing with y=a(x-h)^2+k

h=-1, k=1,a=-3

(h,k)=(-1,1)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up